DISTILASI AIR LAUT TENAGA SURYA DENGAN KONSENTRATOR LENSA FRESNEL - Yudiyanto, Eko; Asrori, Asrori (Universitas Tridinanti Palembang, 2018)
Water supply is a basic need for life. Water management that requires a large amount of cost and energy is needed alternative solutions to produce a cheap process. Research on the distillation process was carried out to find solutions to these problems. The research was carried out by a experiment method to produce a distillation process for water purification. The experiment use an effective fresnel lens of 0.785 m2 and the receiver volume was 200 mLThe results of the study explained that using a fresnel lens concentrator was able to generate steam. The steam can be condensed to produce fresh water. Data from calculation obtained average direct solar radiation is 531.98 Watts/m2 and the power received by the receiver is 346.61 Watt. The average normal solar radiation in tests is 515,7 W/m2. The average temperature of the focus point on the cone receiver is 520,4OC . The wet steam generation process is obtained when the water temperature in the receiver shows 95OC. Experiments of distillation for 200mL sea water needed 10 minutes to reach 4 bar of pressure. Steam is flowed into the condenser so that distilled water is obtained 150 ml.